ANALISIS PEMANFAATAN MEDIA SOSIAL DALAM MEMPROMOSIKAN PRODUK FASHION DI PASAR YA’AHOWU KOTA GUNUNGSITOLI - Zai, Windarni; Zalukhu, Yuterlin; Mendrofa, Yupiter; Zebua, Emanuel (Jurnal Suluh Pendidikan, 2025)
Social media is one of the means of exchanging information between individuals which can also be used as a marketing tool for a business for business actors. Utilization of social media as a means of communication and marketing can increase sales and build brand awareness for customers. The use of social media in promoting fashion products in Gunungsitoli City shows significant potential to increase visibility and sales. This study analyzes social media used in promoting fashion products. This study aims to determine the use of social media in promoting fashion products in the Ya'ahowu market in Gunungsitoli City and the obstacles faced by sellers in promoting fashion products. This study uses a qualitative method. Informants are fashion product sellers and consumers who make buying and selling transactions in the Gunungsitoli City market, where the informants consist of 5 people. The study was conducted by collecting data through interviews, observations and documentation. The results of this study indicate that the Analysis of the Utilization of Social Media in Promoting Fashion Products at the Ya'ahowu Market in Gunungsitoli City can significantly increase product visibility, and show customer satisfaction but also criticism of the effectiveness of the promotion, indicating the need for strategy adjustments to better suit customer needs.